Antibiotics are not needed during tube thoracostomy for spontaneous pneumothorax: an observational case study - DURMUŞOĞLU, LÜTFİYE (BIOMED CENTRAL LTD, 2022)
Background: Usefulness of prophylactic antibiotics following tube thoracostomy remains controversial in the literature. In this study, we aimed to investigate the consequences of closed tube thoracostomy for primary spontaneous pneumothorax without the use of antibiotics. Methods: One-hundred and nineteen patients underwent tube thoracostomy for primary spontaneous pneumothorax. None of them received prophylactic antibiotic treatment. Eight patients with prolonged air leak undergoing either video assisted thoracoscopic surgery or thoracotomy were excluded. Results: Of the remaining 111 ( 104 male and 7 female), 28 (25%) patients developed some induration around the entry site of chest tube that settled without further treatment. White blood cell count was high without any other evidence of infection in 12 (11%) patients and returned to its normal levels before discharge home in all. There was also some degree of fever not lasting for more than 48 hours in 8 (7%) patients. Bacterial cultures from suspected sites did not reveal any significant growth in these patients. Conclusion: Prophylactic antibiotic treatment seems avoidable during closed tube thoracostomy for primary spontaneous pneumothorax. This policy was not only cost-effective but also prevented our patients from detrimental properties of unnecessary antibiotic use, such as development of drug resistance and undesirable side effects.